Left Lung Torsion: Complication of Lobar Resection for an Early Stage Lung Adenocarcinoma - Mansour, Wissam (Case Rep Crit Care, 2016)
Lobar torsion is a fatal but fortunately rare occurrence following lung resection. Early clinical signs and radiographic features may be nonspecific resulting in diagnostic delay. A high index of suspicion is vital for early diagnosis and intervention to avoid further parenchymal necrosis and deadly gangrene. We report a case of left lower lobe torsion in a 76-year-old female following elective upper lobectomy for underlying lung adenocarcinoma. Diagnosis was made following highly suggestive radiographic findings prompting bronchoscopy and revision thoracotomy. An emergency detorsion failed to restore lung viability and was followed by completion pneumonectomy. The patient recovered and was discharged on the seventh postoperative day.